Shocks, Financial Dependence, and Efficiency : Evidence From U.S. and Canadian Industries - Estevao, Marcello; Severo, Tiago (Washington, D.C. : International Monetary Fund, 2011)
The paper investigates how changes in industries' funding costs affect total factor productivity (TFP) growth. Based on panel regressions using 31 U.S. and Canadian industries between 1991 and 2007, and using industries' dependence on external funding as an identification mechanism, we show that increases in the cost of funds have a statistically significant and economically meaningful negative impact on TFP growth. This effect is, however, non-monotonic across sectors with different degrees of dependence on external finance. Our findings cannot be explained by either increasing returns to scale or factor hoarding, as results are not sensitive to controlling for industry size and our calculations account for changes in factor utilization. The paper presents a theoretical model that produces the observed non-monotonic effect of financial shocks on TFP growth and suggests that financial shocks distort the allocation of factors across firms even within an industry, thus reducing TFP growth.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet